2006
DOI: 10.1021/ma061042w
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulation of Uniaxial Tension of an Amorphous Polyethylene-like Polymer Glass

Abstract: Atomistic Monte Carlo (MC) simulations of uniaxial tension of an amorphous linear polyethylene (PE)-like polymer glass have been carried out. A united-atom model has been used where PE chains are represented by beads connected by flexible springs. Highly efficient end-bridging MC moves have been used to first equilibrate the polymer in the melt and then cool to a temperature below its glass transition temperature. A mix of efficient MC moves has also been used to simulate the deformation dynamics. Upon uniaxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
43
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 27 publications
7
43
0
Order By: Relevance
“…a rather slight increase of Young's modulus with pressure has been found. 19 The temperature and strain-rate dependencies of the stress-strain characteristics have been investigated by Li et al 20 They performed atomistic Monte Carlo simulations of uniaxial tension of an amorphous linear polyethylene-like glassy polymer. They found that with increasing strain in the elastic region mechanical work is stored as non-bonded internal energy, and that in the yield regime the intra-chain contributions start to play a role.…”
Section: Introductionmentioning
confidence: 99%
“…a rather slight increase of Young's modulus with pressure has been found. 19 The temperature and strain-rate dependencies of the stress-strain characteristics have been investigated by Li et al 20 They performed atomistic Monte Carlo simulations of uniaxial tension of an amorphous linear polyethylene-like glassy polymer. They found that with increasing strain in the elastic region mechanical work is stored as non-bonded internal energy, and that in the yield regime the intra-chain contributions start to play a role.…”
Section: Introductionmentioning
confidence: 99%
“…24,[26][27][28] Also other simulation techniques are applied to study the deformation of polymers, such as Monte Carlo algorithms or variants of energyminimization methods for PE-alike, 29 polypropylene, 30,31 poly͑oxypropylene͒, 32 PC, [33][34][35] and PE. 36,37 As the simulation studies are limited to only small time and length scales, numerical agreement is often only possible by means of extrapolation over orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of problems such as small system sizes and huge cooling and deformation rates, MD has proved to be a useful tool in studying deformation behavior of amorphous polymers 12, 15, 16. Although Monte Carlo (MC) simulation does not contain any dynamics, this tool is also starting to be used for the study of polymer deformation 17–22. Various lattice‐model MC simulations have been used to study the deformation behavior of polymeric models 19–22.…”
Section: Introductionmentioning
confidence: 99%
“…3‐D off‐lattice MC simulations of PE‐like crosslinked networks have been performed by Chui and Boyce 17. The authors of the present paper recently simulated the uniaxial extension of multichain PE‐like systems employing a mix of very local atomic and more collective MC moves 18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation